Efficacy and Safety of Bifidobacterium Quadruple Viable Bacteria Combined with Mesalamine against UC Management: A Systematic Review and Meta-Analysis. (4th October 2022) - Xie, Fei; Li, Shichao; Fan, Yao; Li, Wusheng; Lv, Qijun; Sun, Xin; Chen, Yingshuang; Yang, Xiangdong
Abstract : Objective. To systematically assess effectiveness and safety of Bifidobacterium quadruple viable bacteria combined with mesalamine against ulcerative colitis (UC) in the Asian population. Methods. An electronic search was conducted in PubMed, Embase, Cochrane Library, CNKI, VIP, and Wanfang databases for a random collection of controlled trials of Bifidobacterium quadruple viable bacteria combined with mesalamine against UC. Following data screening and extraction, a Cochrane risk assessment tool was adopted to evaluate the quality of the included studies, and RevMan 5.3 and Stata/SE 15.1 software were used for meta-analysis. Results. Nineteen articles which enrolled 1, 707 subjects were included ultimately in this study. The experimental group performed better than the control group in improving the Mayo score (MD = − 1.94, 95% CI = − 2.69, − 1.19, P < 0.00001 ), increasing the total clinical efficiency (OR = 5.10, 95% CI (3.53, 7.38), P < 0.00001 ), reducing the levels of IL-8 (SMD = − 1.79, 95% CI (-2.36, -1.12), P < 0.00001 ), increasing the levels of IL-4 (SMD = 1.00, 95% CI (0.60, 1.41), P < 0.00001 ), and reducing the levels of hsCRP (MD = − 3.26, 95% CI (-4.28, -2.25), P < 0.00001 ), TNF- α (MD = − 7.11, 95% CI (-9.23, -5.00), P < 0.00001 ), ox-LDL (MD = − 14.46, 95% CI (-17.20, -11.72), P < 0.00001 ), and LPO (MD = − 3.55, 95% CI (-4.70, -2.39), P < 0.0001 ) as well as increasing SOD level (SMD = 1.68, 95% CI (1.02, 2.35), P < 0.00001 ), and adverse reactions were substantially less than that of control (OR = 0.43, 95% CI = 0.28, 0.66, P = 0.0001 ). Conclusion. In conclusion, the current meta-analysis shows that Bifidobacterium quadruple viable bacterium combined with mesalamine has a satisfactory effect in the treatment of UC in China, and its safety is better than that of mesalamine or Bifidobacterium quadruple viable bacteria alone. However, randomized controlled trials with standardized designs and large sample sizes are still needed for further validation.